2009
DOI: 10.1002/asi.21070
|View full text |Cite
|
Sign up to set email alerts
|

Online supportive interactions: Using a network approach to examine communication patterns within a psychosis social support group in Taiwan

Abstract: A network approach was used to determine the overall supportive communication patterns constructed within the PTT psychosis support group in Taiwan, the largest bulletin board system in the Chinese-speaking world.The full sequences of supportive interactions were observed over a 2 IntroductionHumans need various types of social support at many points in life, especially when they or the ones they care for are in need of health information (Yoo & Robbins, 2008). Individuals purposively acquire health informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 35 publications
6
43
0
Order By: Relevance
“…However, the range of density falls between .01 and .08, which is consistent with findings reported in previous studies of online social support groups (Chang, 2009). Yet although network density followed the expected direction as predicted by Hall's model (Wretch at .05 was larger than MySpace at .04), it did not differ significantly between the two SNSs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the range of density falls between .01 and .08, which is consistent with findings reported in previous studies of online social support groups (Chang, 2009). Yet although network density followed the expected direction as predicted by Hall's model (Wretch at .05 was larger than MySpace at .04), it did not differ significantly between the two SNSs.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, Lewis et al (2008) reported that the average Facebook network density is .22. Chang (2009) found that the densities of most of online support groups ranged between .01 and .08. Compared to those reported in traditional face-to-face settings, online networks were relatively sparse.…”
Section: Network Densitymentioning
confidence: 99%
“…The ETs from Greater Taipei were selected via PTT (telnet://ptt.cc), the largest Bulletin Board System in the world (Chang, 2009). Experienced, in this study, refers to those teachers who have both experience teaching science and a master's degree in science education.…”
Section: Participantsmentioning
confidence: 99%
“…Nurturant support posts provide expressions of caring or concern [30,33,34,38,47,48]. These are summarized in Table 3.…”
Section: Methodsmentioning
confidence: 99%